PENGARUH EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DAN PENGGUNAAN TEKNOLOGI INFORMASI PADA KINERJA INDIVIDUAL DENGAN KEPUASAN KERJA SEBAGAI VARIABEL PEMODERASI - Antasari, Kadek Chendi; Yaniartha Sukartha, Pt D'yan (E-Jurnal Akuntansi, 2015)
This study was conducted to determine the effectiveness of the test results of the effect of accounting information systems and the use of information technology on individual performance and job satisfaction as a moderating variable. The population in this study were 169 employees and samples used were 35 employees who are determined using purposive sampling method. Hypothesis testing method used is multiple linear regression analysis. The results showed that the positive effect between the analysis of information on individual performance, job satisfaction did not moderate the influence of the effectiveness of accounting information systems on individual performance, and job satisfaction also did not moderate the relationship influence the use of information technology on individual performance.
Keywords: Accounting Information Systems Effectiveness, Use of Information Technology, Job Satisfaction, Individual Performance